Peran dan Wewenang Mahkamah Konstitusi dalam Sistem Pemerintahan Indonesia - Aryuni Fitri Djaafara; Jean Claudia; Maulida Syahrin Najmi; Rasji Rasji (Publikasi Indonesia, 2022)
The Constitutional Court is a State Institution Guarding the Constitution which Has the Authority to Decide at the First and Last Levels. As an actor of judicial power, the constitutional function of the Constitutional Court is the judiciary to uphold law and justice. As for the authority of the Constitutional Court that has been listed in Law Number 24 of 2003, namely that the Constitutional Court has the authority to resolve disputes or disputes related to the authority of state institutions that are given authority by the 1945 Constitution of the Republic of Indonesia; Decide the dissolution of political parties; Resolving disputes over the results of general elections; and the Constitutional Court is obligated to issue a decision on the recommendation of the House of Representatives (DPR) that the President and/or Vice President are suspected of having violated the law in the form of treason to the State, having committed bribery, disgraceful acts or actions that do not meet the requirements as President and/or Vice President as regulated in the 1945 Constitution of the Republic of Indonesia.